Analisis Kemampuan Numerisasi pada Siswa Kelas 6 SD N 56/I Desa Aro - Afdiya, Putri; Risdaliani, Risdaliani; Fitriani, Auliya; Nainggolan, Thalia Cahya Nabila; Audianti, Ella; Simbolon, Putri Jayani (Lembaga Yasin AlSys, 2022)
Education in the 21st century which guides students to be able to participate in the development of the times which are full of challenges at this time. Numerization ability is one of the requirements in realizing skills in 21st century education. This research uses a type of qualitative research using descriptive methods. The purpose of this research is to be able to find out students' numerization abilities in learning mathematics. In this study using a form of research that is a case study. The stages in this research are starting from the implementation, preparation and final stages. The instruments used in this study to obtain data were tests and interviews. The results obtained in this study where the ability of students on numerization skills in solving mathematical nemerization ability questions is still moderate. This is evidenced by the results of the average score of the student test scores that have been given where out of 23 students there are 6 students belonging to the low category, 12 students including k in the medium category and 5 students belonging to the high category.